2009
DOI: 10.1111/j.1365-2141.2009.07943.x
|View full text |Cite
|
Sign up to set email alerts
|

Genome wide DNA‐profiling of HIV‐related B‐cell lymphomas

Abstract: Summary Non-Hodgkin lymphomas (NHL) represent a frequent complication of human immunodeficiency virus (HIV) infection. To elucidate HIV-NHL pathogenesis, we performed a genome-wide DNA profiling based on a single nucleotide polymorphism-based microarray comparative genomic hybridization in 57 HIV-lymphomas and, for comparison, in 105 immunocompetent diffuse large B-cell lymphomas (IC-DLBCL). Genomic complexity varied across HIV-NHL subtypes. HIV-Burkitt lymphoma showed a significantly lower number of lesions t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 69 publications
(86 citation statements)
references
References 49 publications
(72 reference statements)
5
67
0
Order By: Relevance
“…Although our analysis is restricted to single loci, our results fit with the presence of a lower number of genomic alterations in EBV-positive diffuse large B-cell lymphoma found by comparative genomic hybridization analysis in cases associated with other sources of immunosuppression (human immunodeficiency virus and post-transplant setting) by other groups. [49][50][51][52] Thus, our results are in line with the concept that both immunosuppression and EBV oncogenic effects in concert may reduce the need of additional chromosomal alterations frequently found in conventional EBV-negative diffuse large B-cell lymphoma.…”
Section: Discussionsupporting
confidence: 77%
“…Although our analysis is restricted to single loci, our results fit with the presence of a lower number of genomic alterations in EBV-positive diffuse large B-cell lymphoma found by comparative genomic hybridization analysis in cases associated with other sources of immunosuppression (human immunodeficiency virus and post-transplant setting) by other groups. [49][50][51][52] Thus, our results are in line with the concept that both immunosuppression and EBV oncogenic effects in concert may reduce the need of additional chromosomal alterations frequently found in conventional EBV-negative diffuse large B-cell lymphoma.…”
Section: Discussionsupporting
confidence: 77%
“…In the immunodeficiency-related DLBCL, the presence of Epstein-Barr virus infection is associated with a lower number of genomic aberrations. 28,29 Although RS arises in the preexisting immunodeficiency associated with CLL, 1 Epstein-Barr virus infection does not play a major role in RS 2,3 and is an unlikely explanation for our data. Epigenetic changes, such as specific methylation patterns, 30 or still-unidentified somatic mutations, might explain the observed relative low genomic complexity in RS vs DLBCL.…”
Section: Discussionmentioning
confidence: 72%
“…A SNP array analysis of HIV-related BL found recurrent gain of 1q (18%) and loss of 17p including TP53 (27%) but not gain of 13q (Capello et al, 2009). Scholtysik et al (2010) reported gains on 1q localized to minimum common regions (MCRs) at 1q21.1 (26%) and 1q31.3 (33%).…”
Section: Array Cgh and Snp Arraysmentioning
confidence: 99%